Sugar Loaf Land in south‐eastern Brazil: a centre of diversity for mat‐forming bromeliads on inselbergs. (17th February 2016) - de Paula, Luiza F. A.; Forzza, Rafaela C.; Neri, Andreza V.; Bueno, Marcelo L.; Porembski, Stefan
Abstract : Inselbergs sensu lato are isolated, mainly granitic and gneissic, rock outcrops, forming old landscape elements on crystalline continental shields on all continents. Mats consisting mainly of monocots occur on open rocky slopes, forming a conspicuous habitat on these outcrops. Brazilian lowland inselbergs consist of species‐rich mats with large numbers of endemics and Bromeliaceae standing out as characteristic elements in these communities. For the first time, we provide a checklist of mat‐forming bromeliads on lowland inselbergs in Brazil and investigate whether the regional species pool influences the species diversity of inselberg mats. Furthermore, through modelling analysis, we looked for the potential distribution of bromeliads endemic to inselbergs, expecting that they would show a narrower niche width than non‐endemic species. Our data indicate the existence of a particular phytogeographical region in the Atlantic Forest in south‐eastern Brazil, comprising inselbergs harbouring a highly diverse flora of Bromeliaceae, which we call Sugar Loaf Land . In addition, our projections reveal smaller predicted areas for bromeliads endemic to inselbergs compared with non‐endemic species, the former apparently being mainly controlled by climatic factors. In addition to climate and regional species pools, the island‐like character of inselbergs seems to play an important role in the speciation of rupicolous Bromeliaceae.